2021
DOI: 10.12688/gatesopenres.13155.2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic gestational age assessment in low resource settings: a validation protocol

Abstract: Preterm birth is the leading global cause of neonatal morbidity and mortality. Reliable gestational age estimates are useful for quantifying population burdens of preterm birth and informing allocation of resources to address the problem. However, evaluating gestational age in low-resource settings can be challenging, particularly in places where access to ultrasound is limited. Our group has developed an algorithm using newborn screening analyte values derived from dried blood spots from newborns born in Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Upon receipt, the samples were visually assessed for quality and considered unsatisfactory if there was insufficient blood, serum rings, or if the sample was clotted, layered, or otherwise overtly damaged. A detailed study protocol can be found here [10].…”
Section: Dbs Collection Shipping and Analysis In Low-resource Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon receipt, the samples were visually assessed for quality and considered unsatisfactory if there was insufficient blood, serum rings, or if the sample was clotted, layered, or otherwise overtly damaged. A detailed study protocol can be found here [10].…”
Section: Dbs Collection Shipping and Analysis In Low-resource Settingsmentioning
confidence: 99%
“…NSO screens for over thirty priority diseases using immunoassays, enzyme assays, high performance chromatography, liquid chromatography-mass spectrometry (LC-MS/MS), Flow Injection Analysis Tandem Mass Spectrometry (FIA-MS/MS), and quantitative real time PCR (qPCR) [10,11]. Sample receipt and analysis were integrated into the existing NSO workflow.…”
Section: Dbs Collection Shipping and Analysis In Low-resource Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed study protocol has previously been published which describes the study sites and provides further details on sample collection and processing [17]. The Kenya study site is located in Kisumu at the KEMRI Centre for Global Health Research, with field sites located in Siaya County, where a maternal-infant demographic surveillance program followed a prospective cohort of pregnant women and their infants in two community hospitals: Siaya County Referral Hospital (SCRH) and Bondo sub-County Hospital (BSCH).…”
Section: Study Settingmentioning
confidence: 99%
“…Further validation of this approach is necessary to determine to what extent local factors may affect metabolic profiles, which in turn could impact the accuracy and generalisability of metabolic-derived estimates of GA. We are currently in the process of implementing and further evaluating this approach to GA estimation in multiple low-resource settings in sub-Saharan Africa and South Asia, including Kenya, Zambia, Zimbabwe, and Bangladesh [ 8 ]. Heel prick and/or cord blood samples are being obtained from infants in these sites and sent to Newborn Screening Ontario laboratories for further analysis.…”
Section: Opportunities From Metabolic Ga Testingmentioning
confidence: 99%